2020
DOI: 10.1016/j.foodchem.2020.126748
|View full text |Cite
|
Sign up to set email alerts
|

Influence of regionality and maturation time on the chemical fingerprint of whisky

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 29 publications
(44 reference statements)
0
12
0
Order By: Relevance
“…Table summarizes the instrument settings of representative HRMS techniques for food analysis. Roullier-Gall et al used flow-injection FT-ICR-MS with high mass accuracy (<0.1 ppm) to characterize the chemical signatures of barrel-aged whiskies, , which found that flavonols, oligolignols, and polyphenol glycosides are important markers of whisky samples during maturation. In addition, novel data acquisition strategies, such as data-dependent acquisition (DDA), data-independent acquisition (DIA), and data-independent all ion fragmentation (AIF), have been applied for obtaining qualitative and quantitative information on food ingredients in parallel.…”
Section: Recent Advances In Mass Spectrometry-based Approachesmentioning
confidence: 99%
“…Table summarizes the instrument settings of representative HRMS techniques for food analysis. Roullier-Gall et al used flow-injection FT-ICR-MS with high mass accuracy (<0.1 ppm) to characterize the chemical signatures of barrel-aged whiskies, , which found that flavonols, oligolignols, and polyphenol glycosides are important markers of whisky samples during maturation. In addition, novel data acquisition strategies, such as data-dependent acquisition (DDA), data-independent acquisition (DIA), and data-independent all ion fragmentation (AIF), have been applied for obtaining qualitative and quantitative information on food ingredients in parallel.…”
Section: Recent Advances In Mass Spectrometry-based Approachesmentioning
confidence: 99%
“…Consequently, spirits' economic value is highly associated with their age [6]. Owing to the commercialization and relatively high costs of aged spirits, counterfeiting these products is common worldwide [7]. Therefore, it is necessary to establish a rapid and accurate method to detect the age of spirits to protect consumers from being deceived concerning the age and quality of the spirits.…”
Section: Introductionmentioning
confidence: 99%
“…Aging of the final distillate is limited to at least three years in wooden casks not exceeding 700-liter capacity. However, the common commercial practice is that aging is much longer, sometimes even longer than 12 years (Roullier-Gall et al, 2020). Particularly for high-quality whisky, aging in a cask is longer than five years.…”
Section: Introductionmentioning
confidence: 99%